Sistema de produção de alface em cultivo convencional e cultivo hidropônico: alimento de qualidade? - Santos, Camila Regina dos (2018)
In the conventional and hydroponic cultivation of lettuce, agricultural defensives and fertilizers are used, which presents concentrations of toxic elements in its composition and may alter the aliment’s quality. Thus, the present study aims to evaluate the content of the heavy metals Cd, Cr, Cu and Pb in soil, nutritive solution and lettuce leaves in the region of Toledo – PR. Samples of lettuce and its substrates were collected from five hydroponic and five conventional proprieties, which were submitted to nitroperchloric digestion for the determination of metal contents through spectrophotometry of atomic adsorption AAS/6300. The experimental delimitation was entirely randomized, with ten treatments and three repetitions, and the results were submitted to variance analysis and to Turkey’s test at 5% significance level; also, the Pearson’s correlation (r) was performed between the variables substrate and lettuce leaves. It was observed that the lettuce studied, in general, presented higher contents of Cd and Cr in the hydroponic cultivation - in which 5 of the hydroponic proprieties, 4 of them presented significantly superior than the conventional ones - according to the Turkey’s test; for the element Cu, significant difference also occurred between the farming methods, however there was significant variance in the cultivation of each property; and for Pb, it was observed that the majority of the samples collected presented higher concentrations than the tolerable limits established by ANVISA - whereas the conventional method presented itself statistically similar between each property, for the hydroponic method, two properties presented themselves significantly superior to the others, and statistically different between each other. When the metal concentrations in the lettuce leaves was compared with the substrate, in general, for both conventional and hydroponic methods the contents in the lettuce didn’t show correlation to the contents in the substrate, which indicate that the contamination may be occurring through the use of agrochemicals and agricultural inputs, used for the control of plagues and diseases, aside from inappropriate management. Thus, it is possible to conclude that the variation in metal concentrations in the same cultivation method is due to the fact that the use of different agrochemicals and fertilizes is allowed, which contain different compositions. Furthermore, the pulverization date previous to sampling of the lettuce may have caused some variations to the composition of the vegetable, as well as inappropriate handling of the aliment.